Persepsi Gen Z terhadap Konten Dakwah Gus Baha tentang Kesederhanaan di TikTok - Faishal Azizi; Nunik Hariyani; Zulin Nurchayati (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines Generation Z's (Gen Z) perception of Gus Baha's da'wah content on simplicity distributed through TikTok. The phenomenon of increasing digital da'wah content consumption by Gen Z forms the significant backdrop, particularly Gus Baha's content which has garnered more than one million views across TikTok channels. This study employs a descriptive qualitative approach using in-depth interview method with three informants aged 15–27 years selected through purposive sampling. Data were analysed using Braun and Clarke's thematic analysis. The theoretical framework comprises Stephen P. Robbins' Perception Theory (selection, organisation, interpretation), Uses and Gratifications Theory (Katz, Blumler, & Gurevitch, 1974), and Stuart Hall's Reception Theory (1980). The findings reveal three main themes: (1) simplicity as a spiritual role model; (2) relevance of da'wah language to Gen Z's materialism issues; and (3) awareness of wealth-orientation risks. All informants demonstrated dominant reading of Gus Baha's simplicity message, interpreting content through spiritual and social frames consistent with their lived experiences. The study concludes that Gus Baha's da'wah content successfully fulfils spiritual, identity, and social-enlightenment gratifications for Gen Z through a simple, contextual, and authentic communicative approach, offering implications for digital da'wah content creators on TikTok.